2020
DOI: 10.3390/metabo10090342
|View full text |Cite
|
Sign up to set email alerts
|

A Metabolomics Workflow for Analyzing Complex Biological Samples Using a Combined Method of Untargeted and Target-List Based Approaches

Abstract: In the highly dynamic field of metabolomics, we have developed a method for the analysis of hydrophilic metabolites in various biological samples. Therefore, we used hydrophilic interaction chromatography (HILIC) for separation, combined with a high-resolution mass spectrometer (MS) with the aim of separating and analyzing a wide range of compounds. We used 41 reference standards with different chemical properties to develop an optimal chromatographic separation. MS analysis was performed with a set of pooled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 52 publications
(64 reference statements)
0
14
0
1
Order By: Relevance
“…Untargeted metabolomics analysis was performed using LC–MS/MS. The data obtained were processed by Compound Discoverer 3.1 (Thermo Fisher Scientific, USA) 49 . The metabolomics software package metaX and metabolomic information analysis processing were used for data preprocessing, statistical analysis, metabolite classification, and functional annotation 50 .…”
Section: Methodsmentioning
confidence: 99%
“…Untargeted metabolomics analysis was performed using LC–MS/MS. The data obtained were processed by Compound Discoverer 3.1 (Thermo Fisher Scientific, USA) 49 . The metabolomics software package metaX and metabolomic information analysis processing were used for data preprocessing, statistical analysis, metabolite classification, and functional annotation 50 .…”
Section: Methodsmentioning
confidence: 99%
“…For compound detection signal to noise ratio (S/N) was kept as 3, and the minimum peak intensity was 10 6 . To assign compound annotation on MS/MS level, three different data sources, such as mzCloud, ChemSpider, and Metabolika, with a mass tolerance of 5 ppm, were used [36]. All the duplicate runs were treated as individual samples in the data analysis.…”
Section: Discussionmentioning
confidence: 99%
“…However, despite this fact and the development of different DPP parameter optimization tools it often suffers from extensive problems. Those include false negative and false positive reports of ion species as well as wrongly reported abundance values and other issues. It should be noted that data pre-processing is not challenging because it is hard to perform, but because it is hard to perform well. This point was laid out by Sindelar et al, who demonstrated why poor performance of data preprocessing could lead to much harder downstream data analysis .…”
Section: Nontargeted Data Analysisincreasing Quality By Multiple Lin...mentioning
confidence: 99%